Prevalence, Serotype, Antibiotic Susceptibility, and Genotype of Salmonella in Eggs From Poultry Farms and Marketplaces in Yangling, Shaanxi Province, China - Li, Wei; Li, Hao; Zheng, Shujuan; Wang, Zewei; Sheng, Huanjing; Shi, Chunlei; Shi, Xianming; Niu, Qinya; Yang, Baowei (Frontiers in Microbiology, 2020)
Poultry products such as eggs provide essential nutrients to the human body and thus play vital roles in the human food network. Salmonella is one of the most notorious foodborne pathogens and has been found to be prevalent in eggs. To better understand the characteristics of Salmonella in eggs, we investigated the prevalence of Salmonella spp. in 814 fresh eggs collected from poultry farms and retail marketplaces in Yangling, Shaanxi Province, China. The serotype, genotype, and antibiotic susceptibilities of 61 Salmonella isolates recovered from the eggs were analyzed. The average detection rate of Salmonella-positive eggs was 5.6%, with 6.6% of the eggs collected from poultry farms and 5.1% from marketplaces. Thirteen serotypes were identified from the 61 isolates, among which S. Typhimurium (24.5%) and S. Indiana (22.9%) were the most prevalent serotypes. Other dominant serotypes included S. Thompson (13.1%) and S. Enteritidis (11.4%), with the remaining nine serotypes detected at low rates (1.6–4.9%). All the Salmonella isolates tested were resistant to sulfisoxazole (100.0%). The majority (77.1%) of the isolates were resistant to nalidixic acid, amoxicillin-clavulanate, and ampicillin, while nearly two-thirds (63.9–68.9%) were resistant to trimethoprim-sulfamethoxazole, kanamycin, tetracyclines, and chloramphenicol. The rate of resistance to ciprofloxacin was 40.1%; the resistance rates to streptomycin, ceftiofur, and ceftriaxone ranged from 21.3% to 26.2%; and those to gentamicin, amikacin, and cefoxitin were relatively low (3.3–16.4%). Forty-nine (80.3%) Salmonella isolates exhibited resistance to multiple antibiotics, 20 (32.8%) of which were resistant to at least 10 antibiotics. Subtyping by pulse-field gel electrophoresis revealed a close genetic relatedness of Salmonella isolates from poultry farms, in striking contrast to the high diversity of the isolates obtained from marketplaces. Isolates of the same serotype always shared identical genotype and antibiotic resistance profiles, even the ones that were recovered from eggs sampled at different locations and times. These findings indicate that diverse Salmonella spp. with high rates of multidrug resistance are prevalent in fresh eggs in the study area. More attention should be paid to egg production, transportation, and storage to prevent foodborne outbreaks caused by Salmonella.